Associations Between Conspiracy Ideation, COVID-19 Conspiracy Ideation with Adherence to Preventive Measures Among Adults in Kuwait: A Cross-Sectional Study - Ahmed Najeeb Albatineh; Nourah K Alajmi (Journal of Biostatistics and Epidemiology, 2023)
Background: A lack of knowledge about COVID-19 has led people to believe in conspiracy theories, their origins, and their purposes.  These theories influence people’s compliance with preventive strategies and accepting vaccination, thus affecting the overall community health. This study investigated the association between compliance with preventive measures, conspiracy ideation, and COVID-19 conspiracy ideation. Methods: Data from 554 participants ≥18 years were collected using a questionnaire distributed over social media platforms. Associations between compliance with preventive strategies and several covariates were investigated. To quantify/test the effect of belief in conspiracy theory and COVID-19 conspiracy while accounting for other covariates, a multiple logistic regression model was implemented to estimate odds ratios (OR) and their 95% confidence intervals (CI). Results: Participants were mainly males (58.3%), employed (61.2%), and Kuwaiti nationals (79.1%) with a median (IQR) age of 32 (20) years. The prevalence of generic conspiracy ideation, COVID-19 conspiracy, and poor compliance with preventive measures were 33%, 28.3%, and 34.7%, respectively.  After adjustment for several covariates, believers in conspiracy theory (aOR=1.97, 95%CI:1.24-3.14), believers in COVID-19 conspiracy (aOR=1.96, 95%CI:1.2– 3.21), compared to none/low believers, were significantly associated with poor compliance with preventive measures. Conclusions: Believers in conspiracy theories and COVID-19 conspiracy theories are significantly more likely to be poorly compliant with preventive measures against COVID-19.  This has a negative effect on the community health. Policymakers need to address conspiracy theories on public platforms which will help promote the adaptation of correct public health practices and preventive strategies leading to better health of the community.